Metal forming and the finite-element method - Kobayashi, Shiro, 1941-; Oh, Soo-Ik; Altan, Taylan (Oxford series on advanced manufacturing, 1989)
1. Introduction. 2. Metal Forming Process. 3. Analysis and Technology in Metal Forming. 4. Plasticity and Viscoplasticity. 5. Methods of Analysis. 6. The Finite Element Method--Part I. 7. The Finite Element Method--Part II. 8. Plane-Strain Problems. 9. Axisymmetric Isothermal Forging. 10. Steady State Processes of Extrusion and Drawing. 11. Sheet Metal Forming. 12. Thermo-Viscoplastic Analysis. 13. Compaction and Forging of Porous Metals. 14. Three Dimensional Problems. 15. Preform Design in Metal Forming. 16. Solid Formulation, Comparison of Two Formulations, and Concluding Remarks.